Where Fire Speaks : a Visit with the Himba. - Shields, Sandra (Arsenal Pulp Press, 2002)
On the wild river that divides Namibia from Angola, members of the Himba tribe herd cattle as they have done for hundreds of years. The women wear thick coils of jewelry and skirts of animal skin; there are monkeys in the palm trees and love birds breed nearby. Where Fire Speaks documents the lives of the Himba, and time spent around the fire, where it is believed their ancestors reside, speaking to them and connecting them to their past. But the world of the Himba sits in the shadow of third-world development and the inevitability of change that threatens their way of life; now, they are more.